Polo-like kinase Cdc5 regulates Spc72 recruitment to spindle pole body in the methylotrophic yeast Ogataea polymorpha - Maekawa, Hiromi; Neuner, Annett; Rüthnick, Diana; Schiebel, Elmar; Pereira, Gislene (eLife, 2017)
Cdc5-dependent SPB regulation is linked to delayed cytoplasmic microtubule organization in Ogataea polymorpha.